Willingness to Pay for a Restored and Protected Watershed: Evidence from the Countryside - Cananua-Labid, Sherrie Ann; Quilatan, Julie Ann M.; Bolante, Lovely Rose A. (UI Scholars Hub, 2025)
Climate change and human activity have severely degraded watersheds, jeopardizing their sustainability. The willingness of residents to pay for watershed management is essential for developing sustainable environmental protection efforts. This study determined the respondents' willingness to pay (WTP) for the restoration and protection (RP) of the Ulot Watershed of Samar Island Natural Park using a double-bounded dichotomous choice contingent valuation approach. The researchers used the Kish grid method to draw respondents from 150 households. The study revealed that families with an average annual income of approximately 2746.70 were ready to contribute 0.78 per month, or 9.36 annually, to the watershed restoration and protection fund. An annual aggregate WTP of 102,259.74 may be collected from the community. Logistic regression analysis also revealed a positive association between age, level of watershed knowledge, and WTP. These findings provide strong evidence that a publicly supported watershed management program for the Ulot Watershed is feasible for local government units. In conclusion, understanding the willingness to pay of the community is crucial for implementing effective watershed management strategies and ensuring the long-term sustainability of the Ulot Watershed.